Urgensi Filsafat Analitik dalam Penyusunan Bahan Ajar Bahasa Arab Berbasis Nilai Moderasi - Rodiatul Maghfiroh; Wildana Wargadinata; Mohammad Shohibul Anwar (Alsina : Journal of Arabic Studies, 2023)
The preparation of Arabic teaching materials based on moderation values has been the focus of this research. The analytic philosophy approach is a foundation for detailing and integrating moderation values into teaching materials. This study aims to identify analytic philosophy's urgency in developing moderation value-based Arabic teaching materials. The analysis method used involves a qualitative approach, which analyzes the content of teaching materials developed using the principles of analytic philosophy. This analysis involves differentiating concepts, language rigor, and understanding cultural contexts. The results showed that analytic philosophy significantly enriched Arabic teaching materials by considering the diversity of students' moderation values. The learning steps applied include careful differentiation of concepts, rigor in the use of language, and continuous reflection and improvement. This research contributes to developing Arabic pedagogy responsive to students' values and culture, creating a framework combining analytic philosophy with moderation values in Arabic teaching approaches.